A mechanics-based method towards risk assessment of RC buildings under tsunami and flow-type hazards. (1st August 2022) - Del Zoppo, Marta; Di Ludovico, Marco; Prota, Andrea
Highlights: the SAFETI method is presented to develop analytical fragility functions for RC frame buildings subjected to tsunami or flow-type hazards; a damage levels classification is proposed for both structural and non-structural (i.e., infill walls) components; damage levels computed through SAFETI are validated with OpenSees for three case-study RC frames subjected to tsunami; analytical fragility curves for a simulated case-study building portfolio subjected to tsunami, flow-type landslides, and flood are derived; Abstract: The study presents a simple mechanics-based method to develop analytical fragility functions for the risk assessment of Reinforced Concrete (RC) frame buildings subjected to tsunami or other flow-type hazards (i.e., flood, mud flows, flow-type landslides, etc.). A harmonized framework for the analysis of building portfolios to flow-type hazards is first illustrated. The mechanics-based method for the performance assessment of RC frames with breakaway infill walls subjected to tsunami and flow-type loads, called SAFETI (Structural Assessment to Flows and Extreme Tsunami Inundation), is then presented. For the large-scale risk analysis, a damage levels classification is adopted for both structural and non-structural (i.e., infill walls) components, based on the HAZUS approach. The flow depth is assumed as Intensity Measure. Damage levels computed through SAFETI are validated with ones obtained from a refined finite-element modelling in OpenSees for three case-study RC frames subjected to tsunami. Finally, an application of the SAFETI method is presented to show the feasibility of the mechanics-based procedure to derive analytical fragility curves for a simulated case-study building portfolio subjected to tsunami, flow-type landslides, and flood. The SAFETI method appears a robust solution to perform a consistent fragility assessment at regional scale for tsunami and flow-type hazards, explicitly accounting for the building-to-building variability with limited modelling and computational efforts.